Trochanteric Femoral Fracture Around a Birmingham Hip Resurfacing Prosthesis: A Case Report and Review of the Literature. Issue 1 (January 2016) - Chou, Daud Tai Shan; Davis, Ben
Abstract : Case: A traumatic nondisplaced periprosthetic trochanteric fracture around a well-fixed and functioning Birmingham Hip Resurfacing prosthesis was managed with a reconstruction intramedullary nail. The surgical procedure provided excellent pain relief, and the patient was able to mobilize with crutches the day after surgery. Follow-up at 1 year confirmed excellent clinical and radiographic results. Conclusion: In a patient with a previously well-functioning hip resurfacing prosthesis, internal fixation rather than revision hip arthroplasty can offer good clinical and radiographic outcomes. The use of a reconstruction intramedullary nail may be a good option for fixing a periprosthetic trochanteric fracture around a Birmingham Hip Resurfacing implant.